А Result of the histo-phatologic examination on edible organs of the livestock around the suspected mining area - Bataa, Bayartogtokh; Burshakhbai, Nurmukhammed; Adilbish, Altanchimeg; Gendenpil, Lkhamjav; Sainnokhoi, Tserenchimed; Pelden, Bolormaa (Mongolian Journal of Agricultural Sciences, 2020)
In the last decade, there is growing concern about the increase in the number of unknown diseases of pasture livestock due to the natural and anthropogenic factors, such as heavy metals and dust exposure. Thus, it is necessary to measure the concentration of heavy metals in different organs of animals, as well as blood parameters assay and histopathology. We have collected samples from different suspected mining areas, using a random sampling method, and selected 15 goats and 15 sheep. The histopathologic study was performed in necropsy, also macroscopic and microscopic analysis were performed on the diseased animals comparing with healthy animals. In this study, 37.3 % of the sheep and 54.6% of the goat samples were found with gross lesions from different organs, while 24% of sheep and 18.6% of goat organs had microscopic change. Through histo-pathology study, small ruminant lungs of livestock from suspected mining areas were found with inflammatory nodules, while other edible organs were changed in a special transition. In conclusion, we assume the dust exposure from the mining area can be the reason behind the dysfunction. Уул уурхайн, хайгуул олборлолтын бүс орчимд бэлчээрлэж байсан малын эд, эрхтэнд эд судлалын шинжилгээ хийсэн дүнгээс Дэлхийн дулааралт, хуурайшилт болон хүний хүчин зүйлийн (байгаль орчинд халтай технологи бүхий уул уурхайн эрчимтэй үйлдвэрлэл, тээвэрлэлт, эмх замбараагүй олборлолт, хог хаягдал г.м) нөлөөлөлд Монгол орны бэлчээрийн мал өртсөний улмаас онош нь тодорхойгүй өвчин, төрөл бүрийн хүнд металлын хордлогот эмгэг илэрч, өвчлөх, үхэх, тоо толгой нь хорогдох зэрэг эдийн засгийн хохирол бүхий тохиолдол сүүлийн жилүүдэд нэмэгдэх хандлагатай болсон. Иймд мал амьтны эд эрхтэнд агуулагдаж буй хүнд металлын агууламжийг тодорхойлохын зэрэгцээ биохими болон эд судлалын шинжилгээ хийх шаардлага урган гарсан. Эд судлалын шинжилгээнд төв аймгийн Заамар сумын алтны хайгуул, олборлолт явуулж буй бүс нутаг орчим бэлчээрлэж байсан 6 хонь, 6 ямаа, Дорноговь аймгийн Улаанбадрах, Зүүнбаян сумын нутаг дэвсгэрт ураны хайгуул, туршилтын олборлолт явуулж буй бүс нутаг болон Айраг сумын жоншны уурхайн олборлолтын бүс нутаг орчим бэлчээрлэж байсан 9 хонь, 9 ямааны эд эрхтнүүдийг хамруулан шинжилгээ хийсэн. Түлхүүр үг: хонь, ямаа, эд судлалын эмгэгт өөрчлөлт, үлэмж ба бичил бүтэц